Postoperative Concurrent Chemoradiotherapy Versus Radiotherapy Alone for Advanced Oral Cavity Cancer in the Era of Modern Radiation Techniques - Kim, Tae Hyung; Cha, In-Ho; Choi, Eun Chang; Kim, Hye Ryun; Kim, Hyung Jun; Kim, Se-Heon; Keum, Ki Chang; Lee, Chang Geol (Frontiers in Oncology, 2021)
Background/Purpose: Surgery followed by postoperative radiotherapy (RT) has been considered the standard treatment for oral cavity squamous cell carcinoma (OCSCC) of advanced stages or with adverse prognostic factors. In this study, we compared the outcomes in patients with OCSCC who received postoperative concurrent chemoradiotherapy (CCRT) or postoperative RT alone using modern RT techniques. Methods: A total of 275 patients with OCSCC treated between 2002 and 2018 were retrospectively analyzed. Adverse prognostic factor was defined as extranodal extension (ENE), microscopically involved surgical margin, involvement of ≥2 lymph nodes, perineural disease, and/or lymphovascular invasion (LVI). In total, 148 patients (54%) received CCRT and 127 patients (46%) received RT alone. More patients in the CCRT group had N3 disease and stage IVB disease (46.6% vs. 10.2%, p<0.001), ENE (56.1% vs. 15.7%, p<0.001), LVI (28.4% vs. 13.4%, p=0.033). Results: With a median follow-up of 40 (range, 5–203) months, there were no significant differences in the 5-year overall survival (OS) and PFS between treatment groups. In the subgroup analysis according to high risk, the concurrent use of chemotherapy showed significantly improved OS in patients with ENE (HR 0.39, p=0.003). Conclusion: Our retrospective study showed that postoperative CCRT group had comparable survival outcomes to those in the RT alone group for advanced OCSCC in the era of modern RT techniques and indicated that concurrent chemotherapy should be administered to patients with ENE. Prospective randomized studies for confirmation are needed.